HIV infection drives proinflammatory adipocyte differentiation in an in vitro model and reveals a new inflammatory pathway - Freiberger, Rosa Nicole; López, Cynthia Alicia Marcela; Sviercz, Franco Agustin; Jarmoluk, Patricio; Palma, María Belén; García, Marcela Nilda; Quarleri, Jorge; Delpino, M. Victoria (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionAdipose tissue regulates metabolic homeostasis and serves as a reservoir for mesenchymal stem cells (MSCs), which differentiate into osteoblasts and adipocytes, balancing bone and lipid metabolism. Bone loss and fat accumulation are common in individuals living with HIV, prompting us to investigate how R5- and X4-tropic HIV modulates adipocyte differentiation and tissue homeostasis using an in vitro model of MSC-derived adipogenesis.MethodsThe study used an in vitro model of MSCs to examine how R5- and X4-tropic HIV strains affect adipocyte differentiation and function. Researchers assessed adipogenesis by analyzing lipid droplet formation, expression of adipogenic transcription factors (C/EBPα, C/EBPβ, PPAR-γ), lipogenic/lipolytic enzymes, SREBPs, cytokine secretion, and the effects of CXCR4 and CCR5 with specific inhibitors.ResultsHIV exposure influences adipogenesis, increasing lipid droplet size in a tropism dependent manner and upregulating key adipogenic factors such as C/EBPα, C/ EBPβ, and PPAR-γ. This process involves the regulation of lipogenic and lipolytic enzymes, lipid droplet-lysosome interactions, and potential lipid droplet mitochondria cross-talk to fuel lipid accumulation. Additionally, HIV modulates sterol regulatory element-binding proteins (SREBPs), which control fatty acid, triacylglycerol, and cholesterol synthesis. Notably, SREBP2 downregulation correlates with increased type I interferons (IFNa2, IFNb1), linking lipid metabolism to immune responses in HIV infection. HIV-infected adipocytes also exhibit an increased leptin/adiponectin ratio and enhanced IL-1b and IL-6 secretion, contributing to the inflammatory state observed in people with HIV. CXCR4 plays a key role in adipocyte differentiation, as its inhibition with AMD3100 reduces adipocyte number, size, and lipid droplet accumulation under X4-tropic HIV exposure. In contrast, CCR5 does not appear to be significantly involved in adipose tissue homeostasis under R5-tropic HIV exposure.DiscussionThese findings, derived from an in vitro model, suggest that HIV alters MSC differentiation into adipocytes, impacting adipose tissue homeostasis and function.